The strength of gut microbiota transfer along social networks and genealogical lineages in the house mouse - Bendová, Barbora; Bímová, Barbora Vošlajerová; Čížková, Dagmar; Daniszová, Kristina; Ďureje, Ľudovít; Hiadlovská, Zuzana; Macholán, Miloš; Piálek, Jaroslav; Schmiedová, Lucie; Kreisinger, Jakub (FEMS microbiology ecology, 2024)
The gut microbiota of vertebrates is acquired from the environment and other individuals, including parents and unrelated conspecifics. In the laboratory mouse, a key animal model, inter-individual interactions are severely limited and its gut microbiota is abnormal. Surprisingly, our understanding of how inter-individual transmission impacts house mouse gut microbiota is solely derived from laboratory experiments. We investigated the effects of inter-individual transmission on gut microbiota in two subspecies of house mice (Mus musculus musculus and M. m. domesticus) raised in a semi-natural environment without social or mating restrictions. We assessed the correlation between microbiota composition (16S rRNA profiles), social contact intensity (microtransponder-based social networks), and mouse relatedness (microsatellite-based pedigrees). Inter-individual transmission had a greater impact on the lower gut (colon and cecum) than on the small intestine (ileum). In the lower gut, relatedness and social contact independently influenced microbiota similarity. Despite female-biased parental care, both parents exerted a similar influence on their offspring's microbiota, diminishing with the offspring's age in adulthood. Inter-individual transmission was more pronounced in M. m. domesticus, a subspecies, with a social and reproductive network divided into more closed modules. This suggests that the transmission magnitude depends on the social and genetic structure of the studied population.
Keywords: střevní mikroflóra; RNA, Ribosomal, 16S; microbiome; Bacteria; Mice; zvířata; inter-individual transmission; Gastrointestinal Microbiome; gastrointestinal tract; RNA ribozomální 16S; mikrosatelitní repetice; mužské pohlaví; relatedness; Microsatellite Repeats; myši; ženské pohlaví; Animals; social contact; Male; Female